Adjustments with running speed reveal neuromuscular adaptations during landing associated with high mileage running training - Verheul, J.; Clansey, A. C.; Lake, M. J. (Journal of Applied Physiology, 2017)
It remains to be determined whether running training influences the amplitude of lower limb muscle activations before and during the first half of stance and whether such changes are associated with joint stiffness regulation and usage of stored energy from tendons. Therefore, the aim of this study was to investigate neuromuscular and movement adaptations before and during landing in response to running training across a range of speeds. Two groups of high mileage (HM; >45 km/wk, n = 13) and low mileage (LM; <15 km/wk, n = 13) runners ran at four speeds (2.5-5.5 m/s) while lower limb mechanics and electromyography of the thigh muscles were collected. There were few differences in prelanding activation levels, but HM runners displayed lower activations of the rectus femoris, vastus medialis, and semitendinosus muscles postlanding, and these differences increased with running speed. HM runners also demonstrated higher initial knee stiffness during the impact phase compared with LM runners, which was associated with an earlier peak knee flexion velocity, and both were relatively unchanged by running speed. In contrast, LM runners had higher knee stiffness during the slightly later weight acceptance phase and the disparity was amplified with increases in speed. It was concluded that initial knee joint stiffness might predominantly be governed by tendon stiffness rather than muscular activations before landing. Estimated elastic work about the ankle was found to be higher in the HM runners, which might play a role in reducing weight acceptance phase muscle activation levels and improve muscle activation efficiency with running training.